E-MODUL BERBASIS I-SPRING SUITE PADA MATERI EKSPRESI DIRI MELALUI HOBI UNTUK MENINGKATKAN LITERASI SDN AMPELGADING 03 - Nashihin Defith Adi Nugroho; Rahutami; Dwi Agus Setiawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The objective of this research is to create a literacy-focused e-module utilizing the iSpring Suite platform, specifically designed for Indonesian language instruction on the themes of hobbies and procedural texts, with the intention of enhancing the learning outcomes of students at SDN Ampelgading 03. Based on observations and interviews, the problem found in the school is that the learning process remains conventional, with limited use of digital learning media, resulting in low student motivation and a lack of independent learning. The research utilizes the Research and Development (R&D) approach guided by the ADDIE framework, encompassing five key phases: analysis, design, development, implementation, and evaluation. The product was developed using PowerPoint and i-Spring Suite, integrated with interactive games from Wordwall, combined with the discovery learning model, and supported by concrete media to deepen the understanding of the material. Validation was carried out by media experts, subject matter experts, and language experts. The validation results showed that the e-module was considered highly feasible by media experts (95%), subject matter experts (95.8%), and language experts (100%). The practicality test by the teacher received a score of 95.58%, while students gave scores of 96.25% (small group) and 95.75% (large group). The effectiveness test results showed an average N-Gain score of 80.6%, categorized as effective. Furthermore, there was a significant increase between the pre-test andpost-test scores, with an improvement of 24.5 points. Thus, the i-Spring Suite-based e-module is effective and practical for enhancing elementary school students' literacy through an interactive and enjoyable learning approach.